2004
DOI: 10.1029/2003gl018933
|View full text |Cite
|
Sign up to set email alerts
|

Coupling instrumental and geological records of sea‐level change: Evidence from southern New England of an increase in the rate of sea‐level rise in the late 19th century

Abstract: [1] We construct a high-resolution relative sea-level record for the past 700 years by dating basal salt-marsh peat samples above a glacial erratic in an eastern Connecticut salt marsh, to test whether or not the apparent recent acceleration in the rate of sea-level rise (SLR) is coeval with climate warming. The data reveal an average SLR rate of 1.0 ± 0.2 mm/year from about 1300 to 1850 A.D. Coupling of the regional tide-gauge data (1856 to present) with this marsh-based record indicates that the nearly three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
142
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(152 citation statements)
references
References 19 publications
9
142
0
1
Order By: Relevance
“…salt-marsh) data (for example Donnelly et al 2004;Gehrels et al 2006). These data mostly indicate an acceleration at the end of the nineteenth or start of the twentieth century (see Woodworth et al 2011, this volume, for a summary and references).…”
Section: Discussionmentioning
confidence: 99%
“…salt-marsh) data (for example Donnelly et al 2004;Gehrels et al 2006). These data mostly indicate an acceleration at the end of the nineteenth or start of the twentieth century (see Woodworth et al 2011, this volume, for a summary and references).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly encouraging results have been obtained for other North American salt marshes. For example, Donnelly et al (2004) suggested a rapid acceleration in the latter part of the 19th century using data from a marsh in eastern Connecticut. However, on inspection of their time series, one concludes that a timing during the early part of the 20th century would be appropriate.…”
Section: Enhancement Of the Sea-level Data Setmentioning
confidence: 99%
“…Use of basal salt-marsh samples that directly overlie an incompressible substrate avoids the influence of compaction (Jelgersma, 1961;Donnelly et al, 2004), but compilations of discrete basal RSL reconstructions typically lack the chronological and vertical precision required to identify sub-millennial trends (see Engelhart and Horton, 2012). Therefore, late Holocene RSL reconstructions rely on samples from a single core of salt-marsh sediment (e.g.…”
Section: Introductionmentioning
confidence: 99%